PEMETAAN PROSES PERENCANAAN OBAT TAHUNAN PUSKESMAS DI KOTA PAYAKUMBUH - , RAHMA YENI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Eight Public Health Centers (Puskesmas) in Payakumbuh City prepared annual drug plan every end of fiscal year. Drug planning included drug selection, compilation, and calculation. It was unknown whether the annual drug planning process included verification, analysis, discussion, and whether an SOP and job description were available. It was also unknown how the process affected the availability and accuracy of the annual drug planning. Objectives: In general, the study aimed to improve Public Health Center annual drug planning process in Payakumbuh City. Specifically, the study aimed to reveal Public Health Center annual drug planning process and its impact on the levels of availability and accuracy of Public Health Center annual drug planning and to prepare a draft of SOP. Methods: Observational case study design. Data were collected retrospectively and prospectively with in-depth interview and observation of Health Center annual drug plan documents and Public Health Center LPLPO 2012. Data were presented descriptively. Results: The eight Public Health Centers prepared annual drug plans in different ways, ranging from the simplest process, i.e. only involved drug storage staff and the Head of Public Health Center as in Padang Karambia, to the very complex process involving all subunits structural rank of Public Health Center such as in Tiakar. However, these did not guarantee that the implementation of annual drug planning was in accordance with the needs of the respective Health Centers. Drug selection process, verification process, analysis to drug needs calculation stage of each Health Centers also varied widely. None of the Health Centers discussed or provided feedback the final drug plans to the staff. In common, the eight Health Centers did not have SOP nor job description for personnel involved in annual drug planning although the process had been conducted bottom up, involving all sub-units of Health Centers, Health Centers, Village Health Posts, Village Maternity Homes and program implementers.